(untitled) - Amon, Evelyne (New York, 2008)
The fourth edition of Vis-à-vis continues the excitement of the innovative third edition with an expanded emphasis on the Francophone world in both the print and media supplements. In the textbook, the new Blog section (which appears in the middle of each chapter) features contemporary language and French and Francophone culture presented in the personal blogs of four characters with different Francophone backgrounds, followed by commentaries by French-speakers from all over the world. Blogs, which are online personal journals, have become hugely popular around the world, and particularly in France where there are approximately three million blogs in existence today. Our new Video Program, filmed specifically for this fourth edition of Vis-à-vis, builds on the stories of each character while serving to support and expand upon the linguistic and cultural content of the chapter as a whole. The Bienvenue dans le monde francophone feature that recurs after every four chapters in the textbook has been broadened to include Louisiana, Morocco, Switzerland, and Tahiti. Minor changes have been made to the scope and sequence. The overall goal of the revision remains the same as that of the third edition: to promote a balanced four-skills approach to learning French through a wide variety of listening, speaking, reading, and writing activities, while introducing students to the richness and diversity of the Francophone world. A beautiful new contemporary design gives Vis-à-vis an appealing look, inspired by real-life personal blogs that are unique and visually stunning.
Keywords: French language,Pháp ngữ; English,Tiếng Anh